Effect of small airways and viscoelasticity on lung mechanics from expiratory occlusion. Issue 2 (2020) - Howe, Sarah L.; März, Melanie; Krüger-Ziolek, Sabine; Laufer, Bernhard; Pretty, Chris; Shaw, Geoffery M.; Desaive, Thomas; Möller, Knut; Chase, J. Geoffery
Abstract: Monitoring the decay rate of airflow in spirometry may be clinically useful. The decay rate is expected to represent a combination of lung elastance and airway resistance. However, the decay rate calculated using the single compartment lung model is not expected to account for slower lung mechanics, such as small airways resistance and tissue viscoelasticity. This study assesses whether the decay rate is affected by these lung mechanics. An exponentially decaying flow was created using a shutter to occlude airflow during passive expiration for 15 healthy subjects. To approximate small airways resistance and viscoelasticity, the gradient of pressure increase (relaxation gradient) during shutter closure was measured. The occlusion resistance, elastance, and decay rate were also calculated for these breaths. None of these mechanics were found to be correlated with the relaxation gradient. The relaxation gradient was also found to be independent of driving pressure. Conversely, the relaxation gradient was found to depend on lung volume. The results of this study suggest using lung mechanics and decay rate to monitor changes in lung condition over time may miss information about changes in the small airways and viscoelastic lung tissue. Thus, it is useful for monitoring large airways disease, but may be ineffective for small airways disease such as ARDS.